HYPNOBIRTHING: A SYSTEMATIC REVIEW OF RELAXATION TECHNIQUES IN REDUCING PRENATAL ANXIETY - Sari, Yona Wia Sartika; Lestari, Risva Aprina Fitri; Pratiwi, Dessy; Nafilata, Ikrimah (Journal of Community Mental Health and Public Policy, 2025)
Background: Anxiety during pregnancy can worsen the health of both mother and fetus if not treated appropriately. Purpose: This study aims to analyze the benefits of hypnobirthing in reducing anxiety in pregnant women. Methods: This study used a systematic review design using the PICO (Population, Intervention, Comparison, Outcome) framework. The search strategy was conducted through electronic databases including PubMed, ScienceDirect, and Google Scholar, with a focus on articles published in the last five years (2021–2025). Keywords used in searches include "hypnobirthing" and "anxiety". Results: The majority of the studies reviewed showed that hypnobirthing techniques effectively lowered pregnant women's anxiety levels, improved relaxation, and contributed to better pain management during childbirth. Conclusion: Hypnobirthing has the potential to be an effective non-pharmacological intervention in supporting the mental health of pregnant women and helping to achieve a calmer and more controlled childbirth experience. Abstrak Latar belakang: Kecemasan selama kehamilan dapat memperburuk kesehatan ibu maupun janin apabila tidak ditangani dengan tepat. Tujuan: Penelitian ini bertujuan untuk menganalisis manfaat hypnobirthing dalam mengurangi kecemasan pada ibu hamil. Metode: Penelitian ini menggunakan desain tinjauan sistematis menggunakan kerangka kerja PICO (Population, Intervention, Comparison, Outcome). Strategi pencarian dilakukan melalui database elektronik termasuk PubMed, ScienceDirect, dan Google Scholar, dengan fokus pada artikel yang diterbitkan dalam lima tahun terakhir (2021–2025). Kata kunci yang digunakan dalam pencarian termasuk “hypnobirthing” and “anxiety”. Hasil: Mayoritas studi yang ditinjau menunjukkan bahwa teknik hipnobirthing secara efektif menurunkan tingkat kecemasan ibu hamil, meningkatkan relaksasi, dan berkontribusi pada manajemen nyeri yang lebih baik selama persalinan. Kesimpulan: Hypnobirthing berpotensi menjadi intervensi non-farmakologis yang efektif dalam mendukung kesehatan mental ibu hamil dan membantu tercapainya pengalaman persalinan yang lebih tenang serta terkontrol.